Dorsal striatal functional connectivity changes in Internet gaming disorder: A longitudinal magnetic resonance imaging study. (30th December 2019) - Lee, Deokjong; Namkoong, Kee; Lee, Junghan; Jung, Young‐Chul
Abstract: Internet gaming disorder (IGD) is a behavioral addiction involving excessive online game use despite negative psychosocial consequences. Unrestricted online gaming may lead to changes in striatal activity and the relationship between the striatum and other cortical regions. This study investigated structural and functional abnormalities involving the striatum through longitudinal follow‐up magnetic resonance imaging (MRI) assessments. Eighteen young males with IGD (mean age: 23.8 ± 2.0 years) and 18 controls (mean age: 23.9 ± 2.7 years) were evaluated. Subjects were reassessed ≥1 year after the first visit (mean follow‐up duration: 22.8 ± 6.7 months), using voxel‐based morphometry and seed‐based resting‐state functional connectivity (FC) analyses in seed regions of the dorsal and ventral striatum. Subjects with IGD had smaller gray matter volume (GMV) in the anterior/middle cingulate cortex compared with controls during initial and follow‐up assessments. They exhibited decreased FC between the left dorsal putamen and left medial prefrontal cortex (mPFC) compared with controls. They exhibited increased FC strength between the right dorsal putamen and right middle occipital gyrus (MOG) during follow‐up. Subjects with IGD showed a significant correlation between changes in the dorsal putamen‐MOG FC and gaming time per day. Young males with IGD showed an altered FC pattern in the dorsal striatum during follow‐up. FC of the dorsal striatum in IGD increased in the mPFC and decreased in the MOG. These findings showed that IGD was accompanied by weakening of prefrontal control and strengthening of the sensorimotor network, suggesting that uncontrolled gaming may be related with functional neural changes in the dorsal striatum. Abstract : Young males with Internet gaming disorder (IGD) were assessed using a longitudinal designed seed‐based resting‐state functional connectivity (FC) analyses in seed regions of the dorsal and ventral striatum. Subjects with IGD exhibited decreased FC between the left dorsal putamen and left media lprefrontal cortex (mPFC) and increased FC strength between the right dorsal putamen and right middle occipital gyrus (MOG) during follow‐up. Our findings showed that uncontrolled gaming may be related with functional neural changes in the dorsal striatum.